Montmorillonite-Chitosan as a Biocomposite Encapsulation for Ibuprofen in Drug Release - Afifi, Muhammad Ridho; Irwandi, Dodi; Safitri, Eka; Syafei, Dedri; Ngapa, Yulius Dala (Journal of Carbazon, 2024)
Ibuprofen is a type of anti-inflammatory drug. However, its use faces challenges in the medical field due to its rapid degradation, low bioavailability, limited solubility, and high permeability. One approach to address these issues is the encapsulation of ibuprofen by coating it with Montmorillonite (MMT) and Chitosan (CS) to control the released dosages of Ibuprofen. MMT and CS were used to coat ibuprofen using four methods. These methods were compared through dispersing MMT in water, mixing with chitosan, and combining ibuprofen under different conditions. Subsequently, tests were conducted on ibuprofen coated with MMT-CS, including morphology, efficiency, and release profile. The most effective method for controlling ibuprofen release was shown in the third method, where MMT-CS was first modified, and then ibuprofen was added to the modified MMT-CS. This method showed the highest encapsulation efficiency of 61.51%, the best release profile with 21.59% ibuprofen release within 90 minutes, and the most uniform encapsulation morphology. These studies indicated that the MMT-CS biocomposite effectively improves ibuprofen release efficiency, potentially enhancing therapeutic outcomes while reducing side effects of ibuprofen.